Gamification: Current Research and Applications. (September 2017) - Doherty, Shawn; Palmer, Evan; Strater, Laura
Gamification is the concept of applying game mechanics to non-game activities (Deterding, Dixon, Khaled, & Nacke, 2011). This concept has received a lot of recent interest from industry and many examples have emerged, especially within the fields of business and marketing, but has grown to encompass such varied examples as health care, training, prosocial behavior, and law enforcement. The purpose of this panel is to discuss some current research and applications of the gamification concept from a varied set of perspectives. The first panelist will describe lessons learned from research on gamification. The second panelist will describe gamification within an industrial context. The third panelist will discuss gamification concepts applied to education. A discussion among panelists and attendees of future trends and needs for gamification is expected.